2020
DOI: 10.21037/atm.2020.03.148
|View full text |Cite
|
Sign up to set email alerts
|

Management of internal carotid artery near-occlusion: the need for updated evidence

Abstract: Near occlusion of internal carotid artery (ICA) is a rare and easily misdiagnosed condition and the decision for revascularisation still remains controversial. We conducted an updated meta-analysis in order to investigate outcomes after carotid endarterectomy (CEA), carotid artery stenting (CAS) or best medical treatment (BMT) in patients with near-occlusion of the ICA. We also aimed to investigate the role of time as a potential moderator of the near-ICA occlusion-stroke rate association. A multiple electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Subgroup analyses showed that the proportion of CNO with full collapse was not the source of high heterogeneity. Antonopoulos et al ( 23 ) concluded that the pooled stroke rate was 1.52% after CEA, 1.80% after CAS, and 8.39% after BMT. A downward trend over time in stroke rates after CAS and BMT could be discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analyses showed that the proportion of CNO with full collapse was not the source of high heterogeneity. Antonopoulos et al ( 23 ) concluded that the pooled stroke rate was 1.52% after CEA, 1.80% after CAS, and 8.39% after BMT. A downward trend over time in stroke rates after CAS and BMT could be discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the current guideline recommendations are based on previous surgical endarterectomy trials data and do not consider contemporary advance in surgical techniques, OMT, or carotid stenting. A recent meta-analysis suggested the risk of stroke was higher in CANO patients receiving OMT alone, compared with those receiving revascularization (OMT 8.4%, endarterectomy 1.5%, CAS 1.8%) 30 . Modification of management guidelines for CANO is therefore necessary, mandating studies to collect more data.…”
Section: Discussionmentioning
confidence: 99%
“…3,9 Therefore, near-occlusions might not be 'rare', as they are often described to be. [10][11][12][13][14][15] Systematic reviews and meta-analyses of near-occlusion either do not present a prevalence estimate, 1-2 present near-occlusion as 'rare', [11][12]15 'relatively rare', [15][16][17] as ≤10% of 'cases' (of varying definition), [15][16][17][18][19][20] or as 20% of ≥70% stenosis. 17 In consecutive studies assessing near-occlusion prognosis, the prevalence of near-occlusion among symptomatic ≥50% carotid stenosis has been 27%-31%, but with possible selection bias.…”
Section: Introductionmentioning
confidence: 99%